2020
DOI: 10.1177/0022429420943137
|View full text |Cite
|
Sign up to set email alerts
|

Examining Relationships Among Concert Band Directors’ Efficacious Sources, Self-Efficacy for Teaching Strategies, and Effective Teaching Skills

Abstract: The purpose of this study was to investigate the extent that concert band directors’ self-efficacy for teaching strategies was influenced by its four sources: mastery experiences, verbal persuasions, vicarious experiences, and physiological state. A secondary purpose was to investigate possible relationships between directors’ self-efficacy and self-perceptions of effective teaching. Participants were high school concert band directors ( N = 610). They responded to the Concert Band Directors’ Self-Efficacy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
(78 reference statements)
1
23
0
Order By: Relevance
“…A reminder email was sent a week after the initial distribution. This sampling procedure and the distribution process were consistent with a previous investigation of concert band directors' perceptions and experiences (Regier, 2020).…”
Section: Questionnaire Distributionsupporting
confidence: 80%
“…A reminder email was sent a week after the initial distribution. This sampling procedure and the distribution process were consistent with a previous investigation of concert band directors' perceptions and experiences (Regier, 2020).…”
Section: Questionnaire Distributionsupporting
confidence: 80%
“…Among instrumental and vocal music teachers, self-perceived social skills and musical ability predicted self-efficacy (Biasutti & Concina, 2018). Furthermore, Regier (2020) found that highly efficacious concert band directors scored their confidence for using effective teaching skills higher than did low-efficacy directors, including skills associated with teacher intensity (Madsen et al, 1992). Overall, the strength of music teachers' efficacious beliefs appears to relate with important professional dispositions and pedagogical behaviors.…”
mentioning
confidence: 94%
“…Alternatively, follow-up feedback after the same teaching strategy demonstration improved participants' efficacious beliefs and implementation of the new teaching strategy. Among concert band directors, observational experiences had no significant influence on self-efficacy for teaching strategies, which could indicate a need for support that improves teaching strategy implementation after observations (Regier, 2020). Similar needs for follow-up discussions or reflections (Prichard, 2017) and contextual guidance (Conway, 2012) after observational experiences have been discussed for preservice music teachers.…”
mentioning
confidence: 97%
See 2 more Smart Citations